Management of Life Skills-Based Islamic Education at Al-Amin Islamic Boarding School Indramayu - As, Suwarno; Subasman, Iman; Aspandi, Ade; Mazaya El Banna, Aini; Makmun, Syukron (IJORER : International Journal of Recent Educational Research, 2025)
The increasing demand for graduates who master both religious knowledge and practical competencies has encouraged Islamic boarding schools to integrate life skills into their educational management. This study analyzes how Al-Amin Islamic Boarding School, a mid-sized rural pesantren in Kandanghaur, Indramayu, manages life skills-based Islamic education, with a distinctive approach that empowers students to be independent and socially responsible. Using a qualitative descriptive design with a case study approach, data were collected through documentation, observation, and institutional profile analysis. The study examines the planning, organizing, implementation, and evaluation stages of life skills programs embedded in the pesantren environment. The findings reveal that innovation emerges in several management aspects: (1) planning emphasizes competencies aligned with rural socio-economic realities, (2) organizing involves structured collaboration between teachers and student mentors, (3) implementation integrates discipline with experiential learning such as agriculture, entrepreneurship training, and leadership practice, and (4) evaluation adopts informal but continuous behavioral assessments to measure student initiative. This study contributes to the underexplored field of rural pesantren management by demonstrating how structured integration of life skills into educational management can balance religious instruction with practical competencies. The Al-Amin model thus offers a replicable framework for advancing Islamic education reform through life skills-based management.